2007
DOI: 10.1080/09243450600797638
|View full text |Cite
|
Sign up to set email alerts
|

The impact of school leadership on school level factors: Validation of a causal model

Abstract: This study aims to contribute to a better understanding of the antecedents and effects of educational leadership, and of the influence of the principal's leadership on intervening and outcome variables. A path analysis was conducted to test and validate a causal model. The results show no direct or indirect effects of educational leadership on student commitment; instead a reciprocal relationship was found between student commitment and strategic leadership. A range of antecedent variables appears to have more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
104
1
10

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(119 citation statements)
references
References 29 publications
4
104
1
10
Order By: Relevance
“…So far, literature on the cognitive perspective of educational administration has mainly focused on principals' thinking about practical problems and how to solve them, and summarized findings on how expertise is developed and on how novices and experts display their knowledge in a school setting (Hallinger, Leithwood, & Murphy, 1993;Leithwood & Steinbach, 1992Stager & Leithwood, 1989). More recent studies (Wassink, Sleegers, & Imants, 2003;Krüger, Witziers, & Sleegers, 2007) have analyzed the impact of the principals' vision and tacit knowledge on their activities. These activities can play a salient role in shaping the school climate.…”
Section: Role Conceptions and Role Priorities Leadership Behavior Amentioning
confidence: 99%
See 2 more Smart Citations
“…So far, literature on the cognitive perspective of educational administration has mainly focused on principals' thinking about practical problems and how to solve them, and summarized findings on how expertise is developed and on how novices and experts display their knowledge in a school setting (Hallinger, Leithwood, & Murphy, 1993;Leithwood & Steinbach, 1992Stager & Leithwood, 1989). More recent studies (Wassink, Sleegers, & Imants, 2003;Krüger, Witziers, & Sleegers, 2007) have analyzed the impact of the principals' vision and tacit knowledge on their activities. These activities can play a salient role in shaping the school climate.…”
Section: Role Conceptions and Role Priorities Leadership Behavior Amentioning
confidence: 99%
“…Principals are faced with both administrative and educational leadership tasks. It is important to know what their vision is on the combination of both tasks and how they consider what has priority in these tasks (Krüger, Witziers, & Sleegers, 2007). Several authors have attempted to define leadership in terms of a portfolio of roles (Mintzberg, 1973;Yukl, 1981).…”
Section: Role Conceptions and Role Priorities Leadership Behavior Amentioning
confidence: 99%
See 1 more Smart Citation
“…After 1999, studies have been based on the examination of relationship between transformational leadership and numerous variables and showed that this style has positive impact on: satisfaction (Griffith, 2004;Leithwood & Jantzi, 2008;Bolger, 2001) motivation (Griffith, 2004;Kruger, Witziers & Sleegers, 2007), commitment (Geijsel, et. al., 2003;Yu, et.…”
Section: Researches Of Transformational School Leadershipmentioning
confidence: 99%
“…al., 2003;Yu, et. al., 2002; professional growth (Kruger, et. al., 2007), eISSN: 2357-1330 Selection and peer-review under responsibility of the Organizing Committee of the conference 500 organizational conditions (Leithwood & Jantzi, 2000), school learning culture (Barnett, McCorminck & Conners, 2001;Kruger, et.…”
Section: Researches Of Transformational School Leadershipmentioning
confidence: 99%